Design and Verification of Aeroengine Rotor Speed Controller Based on U-LADRC. (22nd May 2020) - Chen, Jiajie; Wang, Jiqiang; Liu, Yunxiao; Hu, Zhongzhi
Abstract : Due to the harsh working environment, engine electronic controller (EEC) has limited computing power. Many advanced control algorithms are difficult to be applied in practice because of complexity of calculation. In this paper, a novel aeroengine transient-speed controller with low algorithm complexity is designed by combining linear parameter varying (LPV) model with U-control theory. Aiming at restraining bad performance influence caused by possible disturbance in cruise, linear active disturbance rejection control (LADRC) compensation is integrated as the U-LADRC controller. This new controller is verified in both the digital simulation platform and hardware-in-the-loop (HIL) platform. The experimental results of the HIL platform show that the U-LADRC control algorithm meets the real-time performance of the EEC in the actual aeroengine. It has good transition state control performance and good steady-state antidisturbance ability, which ensures the smooth operation of the engine in the steady state and has a good practical application prospect.